Judicial Review of The Binding Force of Foreign Companies Shares Transfer Upon Control of The Assets in Indonesia - I Gusti Agung Ayu Gita Pritayanti Dinar; I Made Pria Dharsana (Fakultas Hukum, Universitas Warmadewa, 2025)
In the digital industry era, it is very easy for business actors to choose the law of a country where a company will be registered upon various considerations such as the efficiency factor and a range of benefits derived from the chosen law. If a contract involves two legal subjects with different citizenships, then there will be two different legal systems, namely a foreign law and the national law of a particular country. This can certainly lead to international civil law issues, because the parties bring their respective legal systems into the contract. They can choose their national law or a foreign law as long as it does not conflict with public order or the compulsory rules. For agreements with transnational aspects, this choice of law issue becomes important. Not every foreign party feels comfortable if the agreement is construed according to the Indonesian law. A foreign legal forum for an agreement involving Indonesia is valid and binding if it has been agreed upon by the parties and covered in a clause in the agreement. Some business actors prefer and agree to choose the country of Bermuda as the legal home of their company for certain reasons. The research questions investigated in this study are: (i) What is the regulation of transfers of shares of foreign companies incorporated in Bermuda? (ii) Are transfers of shares of foreign companies incorporated in Bermuda legally binding upon the assets of companies domiciled in Indonesia? This study employs the normative legal research method. Normative legal research is guided by the characteristics of the object of the research, yet remains limited by the expected outcome of the norms initially established. The approaches used in this study are (i) the analytical and conceptual approach and (ii) the comparative approach, whereby a comparison is made between the application of the corporate law of Bermuda and the Law of the Republic of Indonesia No. 40 of 2007 on Limited Liability Company. Sources of legal materials used in this study include related literature, journals, articles and theses that are relevant to the subject matter. The theories applied in investigating the problems in this research are the transnational theory and economic-legal theory. Through this research, it will be possible to determine the regulation of transfers of shares of foreign companies incorporated in foreign countries (in this case Bermuda) and the binding force of such transfers upon the assets of companies domiciled in Indonesia.